Injectable Nano Drug Delivery Systems for the Treatment of Breast Cancer - Urmila Kafle; Satish Agrawal; Alekha K. Dash (MDPI AG, 2022)
Breast cancer is the most diagnosed type of cancer, with 2.26 million cases and 685,000 deaths recorded in 2020. If left untreated, this deadly disease can metastasize to distant organs, which is the reason behind its incurability and related deaths. Currently, conventional therapies are used to treat breast cancer, but they have numerous shortcomings such as low bioavailability, short circulation time, and off-target toxicity. To address these challenges, nanomedicines are preferred and are being extensively investigated for breast cancer treatment. Nanomedicines are novel drug delivery systems that can improve drug stability, aqueous solubility, blood circulation time, controlled release, and targeted delivery at the tumoral site and enhance therapeutic safety and effectiveness. Nanoparticles (NPs) can be administered through different routes. Although the injectable route is less preferred than the oral route for drug administration, it has its advantages: it helps tailor drugs with targeted moiety, boosts payload, avoids first-pass metabolism, and improves the pharmacokinetic parameters of the active pharmaceutical ingredients. Targeted delivery of nanomedicine, closer to organelles such as the mitochondria and nuclei in breast cancer, reduces the dosage requirements and the toxic effects of chemotherapeutics. This review aims to provide the current status of the recent advances in various injectable nanomedicines for targeted treatment of breast cancer.